Temporal consistencies in two champion teams of European football? (¿Regularidades temporales en dos campeones del fútbol europeo?) - Pic Aguilar, Miguel (Retos, 2018)
Abstract. The main objective of the work was to analyze the performance carried out by competitive football teams in their respective regular leagues during the 2015-16 season. All matches played by Leicester F.C. as a representative of the Premier League (n = 38) were considered, while Barcelona F.C. was the team representing La Liga (n = 38). Intra and inter championship monitoring of these champion teams was carried out taking into account seven variables: team, location, quality, warnings, changes of players, goals, and final result. The data matrices were constructed and analyzed using variables temporal reference through the Theme data reduction technique (Magnusson, 2000). From the analysis of the specificity of soccer success in two of the best European championships, formulas that are difficult to detect through a superficial look were extracted. Paying attention to the records’ context of appearance justifies a vision braided through a temporality thread. This work’s findings can be used by sports managers in their long-term planning, while in the short and medium-term coaches can also take advantage of them. Optimizing high-level sports performance requires new analytical perspectives to understand how success arises in football. Resumen. El objetivo prioritario del trabajo era analizar el rendimiento protagonizado por equipos competitivos de fútbol en sus campeonatos respectivos de liga regular durante la temporada 2015-16. Se incluyeron todos los partidos del Leicester F.C. representante de la premier league (n=38) mientras que el equipo representante de La Liga fue el Barcelona F.C. (n=38). Se acometió un seguimiento intra e inter campeonato de los equipos campeones atendiendo a cinco variables: equipo, localización, calidad, amonestaciones, cambios de jugadores, goles y resultado final. Las matrices de datos fueron construidas y analizadas mediante el empleo de la referencia temporal de las variables, empleando para ello la técnica de reducción de datos Theme (Magnusson, 2000). Del análisis de especificidad del éxito futbolístico en dos de los mejores campeonatos del panorama europeo se extrajeron fórmulas difícilmente detectables mediante una mirada superficial. Atender al contexto de aparición de los registros justifica una visión trenzada mediante un hilo de temporalidad. Los hallazgos pueden ser aprovechados a largo plazo por directores deportivos en sus planificaciones, mientras que a corto y medio plazo también los entrenadores pueden verse ayudados. Optimizar el rendimiento deportivo de alto nivel precisa de nuevas perspectivas de análisis mediante las que conocer a qué responde el éxito en fútbol.